Traitement de la dissociation dans un trouble de la personnalité limite avec trouble dissociatif de l'identité et trouble de stress post-traumatique complexe : un cas clinique. - Kiepura, Barnabé; Bérubé, Félix-Antoine; Cailhol, Lionel (Sante Mentale au Quebec)
We describe the trajectory of a 24-year-old woman with a history of borderline personality disorder (BPD) and complex trauma who presented with significant dissociative episodes. The initial assessment--including a psychiatric interview, the use of standardized measures (PCL-5, CAPS-5), and collateral information gathering--identified complex post-traumatic-stress disorder (PTSD) comorbid with dissociative identity disorder (DIID) and incomplete diagnostic criteria for BPD. Treatment consisted of an integrated psychiatric and psychotherapeutic approach based on the DBT-PTSD model. After just over one year of follow-up and 45 therapy sessions, the patient was in clinical remission from PTSD, while dissociative episodes attributable to DID persisted at a lower intensity. This case illustrates that response to DBT-PTSD may be favorable in patients with comorbid DID. The one-year follow-up highlights the persistence of dissociative episodes alongside sustained clinical remission of PTSD. The patient also shares her perspective on her therapeutic experience. This is, to our knowledge, the first reported case of the results of DBT-PTSD on a person with both complex PTSD and DID, at one year of follow-up after finishing therapy.